Data on the classification of Pannonian sediments of the Algyő area - Magyar László (Acta mineralogica-petrographica, 1976)
This study deals with the outlined classification of the Pannonian sediments of the Algyő anticline being an intra-basin area explored most accurately by hydrocarbon prospecting bores in Hungary.